Lingkungan Kerja dan Motivasi Pengaruhnya Terhadap Minat Berwirausaha - Syahid Syahid; Masayu Endang Apriyanti (Universitas Indraprasta PGRI, 2019)
This study aims to analyze the influence of the work environment and motivation on the interest in entrepreneurship. This study is a survey research with populations around Jakarta, Bogor, Tangerang, and Bekasi. Samples were taken with a random sampling technique of 85 people. The instrument used is the questionnaire. Data analysis using multiple regression. From the processing of data obtained results: 1). There is a significant effect of work environment and motivation together towards entrepreneurship interest as evidenced by Fh = 6.047 and Sig. = 0.004 <0.05 2). There is no significant effect of the work environment on the interest in entrepreneurship as evidenced by Th = -1.128 and Sig. = 0.263> 0.05 3). There was a significant effect of motivation on the interest in entrepreneurship as evidenced by Th = -3,047 and Sig = 0,003 <0,05.